Soil Nitrous Oxide (N2O) Emission from Integrated Soil Fertility Management in Maize (Zea mays L.) Cropping Systems - Rogito, R.; Karanja, N.; Merbold, Lutz; Necpalova, M.; Six, Johan (International Livestock Research Institute, 2021)
Integrated Soil Fertility Management (ISFM) has been recommended to address challenges of low soil fertility by incorporating locally available organic resources (ORs) together with inorganic nitrogen (N) fertilizers. Despite ISFM success in field trials, there is limited information on ORs contribution to atmospheric greenhouse gas concentrations through N2O emission. A short-term field study was conducted at two sites with different soil types; silt loam (Aludeka) and silty-clay soil (Sidada) to assess the influence of selected ORs on soil N2O emissions. The ORs treatments included; Calliandra carothyrsus (CL), farmyard manure (FYM) and maize stover (MS) with (+N) and without (-N) inorganic N fertilizer. The study also evaluated the relationship between N2O emissions and soil organic carbon, mineral N, total nitrogen, soil temperature, moisture content, soil nitrate (NO3-) and ammonium (NH4+). Relative to the control (0.190.1 Kg N2O-N ha-1), cumulative N2O emissions were significantly (P= 0.01) higher by 6, 9 and 13 fold under MS +N (1.050.8 Kg N2O-N ha-1), FYM +N (1.740.8 Kg N2O-N ha-1) and CL +N (2.541.2 Kg N2O-N ha-1), respectively at the Aludeka site. At Sidada, cumulative N2O emissions were similar across all the treatments (P = 0.149). Approximately 240% and 411% of increase in cumulative N2O emissions across treatments at Sidada and Aludeka, respectively, was related to inorganic N fertilizer application. At Aludeka, cumulative N2O emissions exhibited significant positive relationship with soil NO3-(r = 0.894, P = 0.03) and NH4+ (r = 0.817, P = 0.013), and negatively correlated with soil C: N ratio (r = -0.710, P = 0.049). While at Sidada soil properties did not exhibit significant relationship with cumulative N2O emissions. The study suggests that influence of OR on N2O emissions in maize based-cropping system vary depending on the type of soil and increases when OR are applied in combination with inorganic N fertilizers.